PENGARUH SIZE, INVENTORY INTENSITY DAN KEPEMILIKAN MANAJERIAL TERHADAP EFFECTIVE TAX RATE: (Studi Empiris Pada Perusahaan Sektor Property dan Real Estate di Bursa Efek Indonesia Tahun 2017-2021) - Cherissa Clara; Lilis Karlina (Pusat Riset dan Inovasi Nasional, 2023)
This study aims to analyze the effect of size, inventory intensity and managerial ownership on the effective tax rate in property and real estate sector companies on the Indonesia Stock Exchange for the period 2017-2021. The type of research used in this research is descriptive research using a quantitative approach. The population in this study were property and real estate sector companies on the Indonesia Stock Exchange for the period 2017-2021. The sample determination method uses purposive sampling method, with several predetermined criteria, there are 6 (six) companies with observations for 5 (five) years, so that the total sample is 30 financial statement data. The analysis method used is multiple linear regression analysis method with the eviews 9 (nine) program. The results of the regression test in this study prove that size, inventory intensity and managerial ownership have no effect and are not significant simultaneously on the effective tax rate. While partially size has a significant effect on the effective tax rate, in contrast to inventory intensity and managerial ownership which have no effect to the effective tax rate.